Review of Physical Conditions and Techniques of Karate Athletes - Daviona, Lommya; Irawan, Roma; Umar, Umar; Setiawan, Yogi (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
The problem in this study is to determine the factors that cause the suboptimal performance of Karate Dojo Street Fighter Athletes in Bukittingi City. This study aims to determine the physical condition and technique of Karate Dojo Street Fighter Athletes in Bukittingi City. This type of research is descriptive statistics. The population in this study consisted of 15 male and 5 female Karate Dojo Street Fighter athletes in Bukittingi City. Sampling in this study used the census method, where all athletes were used as samples, with a total of 20 athletes. The research instrument used a test consisting of aerobic endurance with a 15-minute Balke Test run test, leg muscle explosive power measured by the standing board jump test, speed measured by a 20m sprint, agility measured by side step, punching technique measured by gyaku tsuki. The data obtained were then analyzed using descriptive statistical methods (frequency tabulation), with the formula P = F / N x 100%. The results of this study show that the abilities of Karate Dojo Street Fighter Athletes in Bukittingi City on all assessment indicators can be categorized as good / very good. Based on this, it can be suggested for other dojos in Bukittinggi city to improve their physical condition, improve their aerobic endurance through long-distance running and long-distance walking, improve their speed through speed play training, improve their punching ability through gyaku tsuki combination training, and be more active in training both during training and outside of training hours.